Three mutually tangent circles in a triangle

Geometry Level 4

The figure shows three mutually tangent circles in a 3 3 - 4 4 - 5 5 right triangle. If the radius of the red circle can be expressed as a + b a c b \dfrac{a + \sqrt{b} - \sqrt{a} - \sqrt{c}}{b} , where a a , b b , and c c are positive integers, submit a + b + c a+b+c .


The answer is 17.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Fletcher Mattox
Oct 16, 2020

There is exactly one way to inscribe three mutually tangent circles in a triangle. Such circles are called Malfatti circles and have an interesting history. There are several formulae (which I won't prove) for calculating their radii, but perhaps the most convenient are described here . Call the three radii r a , r b , r_a, r_b, and r c r_c , and take r a r_a as the red circle.

r a = r ( 1 + tan B 4 ) ( 1 + tan C 4 ) 2 ( 1 + tan A 4 ) , r_a = \dfrac{ r(1+\tan \frac{B}{4}) (1+\tan \frac{C}{4}) }{2(1+\tan \frac{A}{4} )} , \enspace r b = r ( 1 + tan A 4 ) ( 1 + tan C 4 ) 2 ( 1 + tan B 4 ) , r_b = \dfrac{ r(1+\tan \frac{A}{4}) (1+\tan \frac{C}{4}) }{2(1+\tan \frac{B}{4}) } , \enspace r c = r ( 1 + tan A 4 ) ( 1 + tan B 4 ) 2 ( 1 + tan C 4 ) r_c = \dfrac{ r(1+\tan \frac{A}{4}) (1+\tan \frac{B}{4}) }{2(1+\tan \frac{C}{4}) }

Where r r is the inradius of A B C = 2 area perimeter = 12 12 = 1 \triangle{ABC} = \dfrac{2\cdot\text{area}}{\text{perimeter}} = \dfrac{12}{12} = 1

Let A = C A B , B = A B C , C = B C A A = \angle{CAB},\enspace B = \angle{ABC},\enspace C = \angle{BCA}

A = π 2 tan ( A 4 ) = 2 1 , B = cos 1 ( 4 5 ) tan B 4 = 10 3 , C = cos 1 ( 3 5 ) tan ( C 4 ) = 5 2 A = \frac{\pi}{2} \implies \tan (\frac{A}{4} )= \sqrt{2} - 1, \hspace{2mm} B = \cos^{-1}(\frac{4}{5})\implies \tan\frac{B}{4} = \sqrt{10} - 3, \hspace{2mm} C = \cos^{-1}(\frac{3}{5}) \implies \tan(\frac{C}{4}) = \sqrt{5} - 2

Thus r a = ( 1 + 10 3 ) ( 1 + 5 2 ) 2 ( 1 + 2 1 ) = 5 + 2 5 10 2 0.5079 r_a = \dfrac{(1+\sqrt{10}-3)(1+\sqrt{5}-2)}{2(1+\sqrt{2}-1)} = \dfrac{5 + \sqrt{2} - \sqrt{5} -\sqrt{10}}{2} \approx 0.5079

So a + b a c b a = 5 , b = 2 , c = 10 , and a + b + c = 17 \dfrac{a + \sqrt{b} - \sqrt{a} - \sqrt{c}}{b} \implies a=5, b=2, c=10, \text{and }a+b+c = \boxed{17}

Me too, I used the formulae from this interesting paper of this 11th grade(!) boy Emil Kostadinov that you mentioned. For the trigonometric calculations of tan x 4 \tan \dfrac{x}{4} , I used twice the formula tan x 2 = 1 + 1 + tan 2 x tan x \tan \dfrac{x}{2}=\dfrac{-1+\sqrt{1+{{\tan }^{2}}x}}{\tan x} . In this same paper, one can find what is needed for solving my problem Is it the smallest?

Thanos Petropoulos - 7 months, 4 weeks ago

Log in to reply

How he wrote that in the 11th grade is beyond me. Apparently I didn't learn enough from it because I got your problem wrong! I was so certain I got it right that I filed a report. :). (later deleted). I may describe my error later. We do seem to be traveling in the same "circles", don't we?

Fletcher Mattox - 7 months, 4 weeks ago
Chew-Seong Cheong
Oct 17, 2020

Let the radii of the red, blue, and green circles be r 1 r_1 , r 2 r_2 , and r 3 r_3 respectively. Then we note that for side A B AB :

r 1 + ( r 2 + r 1 ) 2 ( r 2 r 1 ) 2 + r 2 cot B 2 = A B Since tan B 2 = 1 2 r 1 + 2 r 1 r 2 + 2 r 2 = 3 \begin{aligned} r_1 + \sqrt{(r_2+r_1)^2 - (r_2-r_1)^2} + r_2 \blue{\cot \frac B2} & = AB & \small \blue{\text{Since }\tan \frac B2 = \frac 12} \\ \implies r_1 + 2\sqrt{r_1r_2} + 2r_2 & = 3 \end{aligned}

We get similar equations for the other two sides and we have the three equations as follows:

{ r 1 + 2 r 1 r 2 + 2 r 2 = 3 . . . ( 1 ) r 1 + 2 r 3 r 1 + 3 r 3 = 4 . . . ( 2 ) 2 r 2 + 2 r 2 r 3 + 3 r 2 = 5 . . . ( 3 ) \begin{cases} \begin{aligned} r_1 + 2\sqrt{r_1r_2} + 2r_2 & = 3 & ...(1) \\ r_1 + 2\sqrt{r_3r_1} + 3r_3 & = 4 & ...(2) \\ 2r_2 + 2\sqrt{r_2r_3} + 3r_2 & = 5 & ...(3) \end{aligned} \end{cases}

Solving the quadratic equation ( 1 ) (1) for r 2 \sqrt{r_2} , we have r 2 = 6 r 1 r 1 2 \sqrt{r_2} = \dfrac {\sqrt{6-r_1}-\sqrt{r_1}}2 . Solving equation ( 2 ) (2) , r 3 = 12 2 r 1 r 1 3 r_3 = \dfrac {\sqrt{12-2r_1}-\sqrt{r_1}}3 .

From ( 1 ) + ( 2 ) ( 3 ) (1)+(2)-(3) :

r 1 + ( r 2 + r 3 ) r 1 r 2 r 3 = 1 r 1 + ( 3 + 2 2 ) r 1 ( 6 r 1 ) 5 r 1 6 6 2 ( 1 + 2 ) r 1 ( 6 r 1 ) + ( 1 2 ) r 1 6 = 1 2 r 1 + ( 4 + 3 2 ) r 1 ( 6 r 1 ) 6 2 = 6 \begin{aligned} r_1 + (\sqrt{r_2}+\sqrt{r_3})\sqrt{r_1} - \sqrt{r_2r_3} & = 1 \\ r_1 + \frac {(3+2\sqrt 2)\sqrt{r_1(6-r_1)}- 5r_1}6 - \frac {6\sqrt 2-(1+\sqrt 2)\sqrt{r_1(6-r_1)}+(1-\sqrt 2)r_1}6 & = 1 \\ \sqrt 2 r_1 + (4+3\sqrt 2)\sqrt{r_1(6-r_1)} - 6\sqrt 2 & = 6 \end{aligned}

( 4 + 3 2 ) r 1 ( 6 r 1 ) = 6 ( 1 + 2 ) 2 r 1 ( 34 + 24 2 ) ( 6 r 1 r 1 2 ) = 108 + 72 2 12 ( 2 + 2 ) r 1 + 2 r 1 2 ( 18 + 12 2 ) r 1 2 6 ( 19 + 13 2 ) r 1 + 54 + 36 2 = 0 ( 3 + 2 2 ) r 1 2 ( 19 + 13 2 ) r 1 + 9 + 6 2 = 0 r 1 2 ( 5 + 2 ) r 1 + 3 = 0 \begin{aligned} \implies (4+3\sqrt 2)\sqrt{r_1(6-r_1)} & = 6(1+\sqrt 2) - \sqrt 2 r_1 \\ (34+24\sqrt 2)(6r_1 - r_1^2) & = 108 + 72\sqrt 2 - 12(\sqrt 2 + 2)r_1 + 2r_1^2 \\ (18+12 \sqrt 2)r_1^2 - 6(19+13\sqrt 2)r_1 + 54 + 36\sqrt 2 & = 0 \\ (3+2 \sqrt 2)r_1^2 - (19+13\sqrt 2)r_1 + 9 + 6\sqrt 2 & = 0 \\ r_1^2 - (5+\sqrt 2)r_1 + 3 & = 0 \end{aligned}

r 1 = 5 + 2 27 + 10 2 12 2 = 5 + 2 5 ( 3 + 2 2 ) 2 = 5 + 2 5 10 2 \begin{aligned} \implies r_1 & = \frac {5+\sqrt 2 - \sqrt{27+10\sqrt 2-12}}2 = \frac {5+\sqrt 2 - \sqrt{5(3+2\sqrt 2)}}2 \\ & = \frac {5+\sqrt 2 - \sqrt 5 - \sqrt{10}}2 \end{aligned}

Therefore a + b + c = 5 + 2 + 10 = 17 a+b+c = 5+2+10 = \boxed{17}

This is the solution I wanted to write, but somehow couldn't quite see it. Most helpful. Thank you. I think equation (3) should = 5, not 3.

Fletcher Mattox - 7 months, 4 weeks ago

Log in to reply

Glad that you like it. I have changed it to 5.

Chew-Seong Cheong - 7 months, 3 weeks ago
Vinod Kumar
Nov 13, 2020

Let x be red, y be blue and z be green circle radius. Write the following

x+2√(xz)+z/[tan(C/2)]=4, tan(C)=3/4

x+2√(xy)+y/[tan(B/2)]=3, tan(B)=4/3

y/[tan(B/2)]+z/[tan(C/2)]+2√(yz)=5

Solve using WolframAlpha

x=(1/2)[5+√2−√5−√10]

Answer=17

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...